PENGARUH KOMPETENSI PROFESIONAL GURU TERHADAP HASIL BELAJAR PESERTA DIDIK KELAS V DI MIN NAGEKEO - Muhammad Ikhsan; Syahruddin; Rosdiana; M Mirza Fatahullah (JIPMI (Jurnal Ilmiah Pendidikan Madrasah Ibtidaiyah), 2022)
This study aims to determine the effect of teacher professional competence on the learning outcomes of fifth grade students at Madrasah Ibtidaiyah Negeri Nagekeo, Nagekeo Regency, East Nusa Tenggara Province. This research consists of two variables, namely the independent variable, namely the professional competence of teachers and the dependent variable, namely learning outcomes. This quantitative research uses an ex post facto type of research conducted on 56 fifth grade students with saturated sampling sampling technique, using questionnaires and documentation as research instruments, then the data is analyzed using statistics, both descriptive statistics and simple regression statistics. Based on the results of the descriptive analysis, the results of the professional competence knowledge of class V teachers at Madrasah Ibtidaiyah Negeri Nagekeo are in a moderate position, which is 64%, while the results of research on learning outcomes for class V students at Madrasah Ibtidaiyah Negeri Nagekeo are in a moderate position, namely 52%. the calculation is obtained ((tcount) = 13.372 while (ttable) = 1.67 for a significance level of 0.05%. Because tcount is greater than ttable, it can be concluded that H0 is rejected and H1 is accepted. This means that there is an influence of teacher professional competence on student learning outcomes. class V at Madrasah Ibtidaiyah Negeri Nagekeo, Nagekeo Regency, East Nusa Tenggara Province.